Enfoque social del manejo de pie diabético desde la atención primaria de salud - Mileidys González Cedeño; Maricela Alfonseca Guerra; Mayelin Hernández Rodríguez (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
One of the complications of Diabetes Mellitus is the diabetic foot, for many authors the most devastating, which sometimes leads to limb mutilation, resulting in a health problem with great social impact. In the prevention of diabetic foot, primary care is a fundamental link. Improving knowledge of the patient and family in foot care favors behaviors that enhance protection, increase motivation and consolidate skills for the prevention and treatment of this disease. A documentary review was carried out in Spanish and English based on the information obtained from texts and magazines consulted in reference centers, through electronic locators with the aim of substantiating the theoretical aspects related to the management of the diabetic foot in primary care from a social approach. The sources consulted agree on the importance of theoretical knowledge about the social bases of the disease and its management in primary care, which will allow the design of educational actions for promotion and prevention, to intervene in the population in order to modify the style of life and prevent the appearance of Diabetic Foot based on primary education.